Advances in Environmental Monitoring and Assessment - Sarvajayakesavalu, Suriyanarayanan (IntechOpen, 2019)
The book Advances in Environmental Monitoring and Assessment is a collection of the latest research techniques on environmental monitoring and assessments. I believe that the information contained in this book will enhance the skills of environmental scientists and decision makers and contribute to the exchange of best practices for developing and implementing optimum methods for environmental assessment and management.